PERKEMBANGAN SOSIAL EMOSIONAL ANAK BROKEN HOME USIA 4 TAHUN DI DESA SUKAPURA KABUPATEN PROBOLINGGO - Siti Maslahah Maslahah; Laily Sofya Isnaini; Benny Prasetiya (Al-ATHFAL: Jurnal Pendidikan Anak, 2023)
Early education for children is family. in the family environment what should and should not be done, and what is appropriate and inappropriate to do, and other values. Where the development of a child is greatly influenced by the immediate family, especially both parents.In terms of children's cognitive, emotional and psychomotor development.Because the initial education of a child is his family. Parents are a child's earliest teacher. This research is qualitative in nature; Through a description by conducting interviews and observations, the results of the study show that cases of broken homes that often occur in Sukapura Village, Probolinggo Regency are early marriage and the selfishness of parents who are victims of children which has a negative impact on children's social emotional development. some children have difficulty controlling emotions and it is difficult to socialize with the surrounding environment.